Information Technology and the Structuring of Organizations - Bagla, Ashish; Gupta, Vivek (Journal of Commerce and Trade, 2011)
A lot of money is invested by organization to develop a meaningful information system that can serve their purpose. But the status of end user and their information required present a set of unique and different problem that need to be overcome. The environmental success of this kind of information system model is affected by various factors like people, activity and system involved in development cycle, apart from the rest of element used in their development cycle.This paper in prepared to develop effective computerized information system model by displaying how the people, activity, and system can influence the model by associating or non associating with the model. This paper also highlights the relation between these factors. The element making up the framework can be summarized in 3 words: people, activities and systems. These elements form the main components of the information system model. They are the elements within an organization, which have an effect on and describe the development and usage of information system model. The framework is described using set theory. Each of these 3 components is assumed as sets containing element present in an organization during system development.